Wacana Isu-isu Kontroversi Berkaitan Islam: Satu Analisis Akhbar-akhbar Terpilih Di Malaysia - Mohd Sofian, Muhammad Raqib (2021)
Newspapers do not operate in vacuum and it is seen as a medium for structuring the production of meaning in society. Newspapers especially those owned by the government have certain ideologies to convey to the general public in order to maintain a specific existing social order. Particularly in Malaysia, Islam is used as a hegemonic tool by the government to continue dominating the mind-set of the lower class by using religion as a political weapon to gain power and maintaining the status quo. This causes the controversial issues pertaining to Islam to be frequently discussed in the news media in tandem with the vested interest of those owning the newspapers. Thus, this study aims to identify reporting patterns, newspaper discourses and factors that influence the production and reporting on controversial issues involving Islam in the mainstream and alternative press in Malaysia. Controversial issues involving Islam that are chosen in this study are (a) the issue of organizing a program known as Seksualiti Merdeka in 2011, (b) the issue on the use of the word “Allah” in 2013, (c) the issue of the amendment of Syariah Criminal Code Enactment II 1993 in Kelantan or known as hudud in 2015 and (d) the issue of organizing an alcohol festival known as “Better Beer Festival” and Octoberfest in 2017. These four issues are chosen as case studies because these issues sparked widespread debates among members of society and received extensive media coverage in Malaysia.